RESISTÊNCIA TÉRMICA DE CAVIDADES DE AR HORIZONTAIS E FECHADAS PARA APLICAÇÕES EM EDIFICAÇÕES - Güths, Guilherme Larsen; Güths, Saulo; Michels, Caren (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
It is known that the greatest heat gain in ground-level buildings is due to the roof, so the use of radiant barriers is being increasingly diffused in civil engineering in order to minimize the heat flow through the covering system. However, there is still no technical normalization that addresses the issue, so there are products that appear in the market without actually presenting a low emissivity, although they have characteristic of a radiant barrier. The tests commonly performed to qualify such products often lack outstanding properties of the samples, to rectify these inaccuracies it is proposed to reformulate the methods of experimentation. When applying the concept of Equivalent Thermal Resistance the ability to measure a much higher degree of parity is obtained in relation to the actual cases of application.